Between Pleasures and Risks: The Circulation of Knowledge about Food in French Primary Schools - De Iulio, Simona; Kovacs, Susan (The International Journal of Sociology of Agriculture and Food, 2014)
Pleasures and risks associated with food are not stable entities but are constantly negotiated as elements of a network of social interactions. Educational, medical, commercial and political discourses play a determining role not only in the perception, but also in the configuration and circulation of the categories of pleasures and risks. Few studies have investigated the circulation of knowledge and values related to food from a communicational and informational perspective. This article aims at exploring how the tension between pleasure and risk characterizes discourses on food produced for school children by different actors: food companies, textbook editors, educators. Our considerations are based on an exploratory and qualitative study of information and communication devices related to food made available to teachers and pupils in the French region Nord-Pas de Calais. The messages in these devices correspond to often divergent trends and discursive positions. We will consider the presence of sensualist and responsibilizing discourses on food as they place children at the centre of a constellation of interacting voices promoting a range of concerns, types of engagement and forms of knowing.